Preliminary report of a gas conditioner to improve operational reliability of cryotherapy in developing countries - Broekhuizen Fredrik; Sellors John; Seamans Yancy; Howard Michelle (BMC, 2006)
Abstract Background Cryotherapy is a safe, affordable, and effective method of treatment for cervical intraepithelial neoplasia. In some low-resource settings, environmental conditions or qualities of the refrigerant gas can lead to blockage of cryotherapy equipment, terminating treatment. A prototype of a gas conditioner to prevent operational failure was designed, built, and field tested. Methods The prototype conditioner device consists of an expansion chamber that filters and dries the refrigerant gas. Users in Peru and Kenya reported on their experience with the prototype conditioner. In Ghana, simulated cryotherapy procedures were used to test the effects of the prototype conditioner, as well as the commonly used "cough technique." Results Anecdotal reports from field use of the device were favorable. During simulated cryotherapy, the prevalence of blockage during freezing were 0% (0/25) with the device alone, 23.3% (7/30) with the cough technique alone, 5.9% (1/17) with both, and 55.2% (16/29) with neither (Pearson's Chi square = 26.6, df = 3, p < 0.001 (comparison amongst all groups)). Conclusion This prototype design of a cryotherapy gas conditioner is a potential solution for low-resource settings that are experiencing cryotherapy device malfunction.